Simplified LDPC-assisted CNC algorithm for entropy-loaded discrete multi-tone in a 100G flexible-rate PON - Mo, Wenxuan; Zhou, Ji; Liu, Gengchen; Huang, Yuanda; Li, Liangchuan; Cui, Han; Wang, Haide; Lu, Qingxin; Liu, Weiping; Yu, Changyuan (Optics express, 2023)
Passive optical networks (PONs) have been widely used in optical access networks to meet the requirement of the rapidly growing data traffic. However, the optical power budget of the worst optical network unit certainly limits the maximum capacity of PON. In this paper, we demonstrate a flexible-rate PON based on entropy-loaded clipping discrete multi-tone (DMT) for increasing the capacity. Meanwhile, clipping operation and simplified low-density parity-check (LDPC) assisted clipping-noise-cancellation (CNC) algorithm are proposed to improve the performance of DMT in peak-power constrained PON. In the simplified LDPC-assisted CNC algorithm, the iteration number of the sum-product algorithm in the LDPC decoding can be reduced to decrease the computational complexity almost without performance loss. The experimental results show that the simplified CNC algorithm can achieve approximately 1.8dB improvement of the optical receiver sensitivity at the 20% soft-decision forward-error-correction limit. The proposed flexible-rate PON has a wide-range data-rate adjustment from 12.5Gb/s to 100Gb/s under the optical power budget from 40dB to 26dB.